Patterns of inclusion and exclusion among trans women in South Africa: a critical narrative inquiry - Shabalala, Siyanda Buyile (Rhodes University, Faculty of Humanities, Department of Psychology)
Trans women have for the most part remained grossly marginalised in gender development frameworks that have concerned themselves with resolving the historical disenfranchisement of women in patriarchal societies. Considering this continuing systemic erasure of trans subjectivity, this study has aimed to foreground transness, engaging trans women's experiences of inclusion and exclusion to better understand the traditionally oppressive institutionality of gender in South Africa from a historically silenced trans standpoint. Semi-structured individual interviews were conducted with five trans women living in South Africa. Data was transcribed and analysed using narrative analysis. Mapping the structures, practices and norms that contribute to the marginalisation of trans women in South Africa, the study found that trans women face economic vulnerability driven by familial rejection along with structural discrimination in a gender-biased labour system. Furthermore, trans women were revealed to contend with institutional erasure and stigmatisation in sex-segregated healthcare structures as well as invisibilisation in cisnormative South African knowledge systems that underrepresent trans identities and their viewpoints of the world. Underlyingly, the societal exclusion of trans women emerged as centrally organised by a structure of genderism that rigidly assumes the binariness and fixedness of gender, principally in ways that restrict trans women's right to self-determine as women. Genderism was observed to collude with factors of race and class in a largely capitalist post-apartheid South African society, working concurrently and jointly to reinforce the social exclusion of trans women. However, often subtle narratives of trans social inclusion located marginalising cisgender power in South African democracy as contested terrain.
Keywords: Transgender women -- South Africa; Genderism; Social inclusion; Social integration; Social exclusion; Social isolation; Narrative